2014
DOI: 10.1158/0008-5472.can-13-2424
|View full text |Cite
|
Sign up to set email alerts
|

Nutlin-3a Efficacy in Sarcoma Predicted by Transcriptomic and Epigenetic Profiling

Abstract: Nutlin-3a is a small-molecule antagonist of p53/MDM2 that is being explored as a treatment for sarcoma. In this study, we examined the molecular mechanisms underlying the sensitivity of sarcomas to Nutlin-3a. In an ex vivo tissue explant system, we found that TP53 pathway alterations (TP53 status, MDM2/MDM4 genomic amplification/mRNA overexpression, MDM2 SNP309, and TP53 SNP72) did not confer apoptotic or cytostatic responses in sarcoma tissue biopsies (n ¼ 24). Unexpectedly, MDM2 status did not predict Nutlin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
(54 reference statements)
1
18
0
Order By: Relevance
“…This observation facilitates the design of a RG7112 clinical trial in GBM, as the burden of reassessing MDM2 and TP53 statuses at recurrence could be avoided. However, others have proposed that a larger epigenetic and expression profiling of a subset of TP53 target genes should be used to predict treatment response instead of the traditional MDM2 amplified/ TP53 wild-type profile [43]. Interestingly, in our study, we observed that a subset of PDCLs that carried a CDKN2A homozygous deletion together with wild-type TP53 were more sensitive than CDKN2A wild-type lines.…”
Section: Discussionmentioning
confidence: 55%
“…This observation facilitates the design of a RG7112 clinical trial in GBM, as the burden of reassessing MDM2 and TP53 statuses at recurrence could be avoided. However, others have proposed that a larger epigenetic and expression profiling of a subset of TP53 target genes should be used to predict treatment response instead of the traditional MDM2 amplified/ TP53 wild-type profile [43]. Interestingly, in our study, we observed that a subset of PDCLs that carried a CDKN2A homozygous deletion together with wild-type TP53 were more sensitive than CDKN2A wild-type lines.…”
Section: Discussionmentioning
confidence: 55%
“…The potential now offered by the PDE model is ‐omic analysis of matched treated and untreated samples using the PDE model. Our teams have published transcriptomic and proteomic analysis of PDE tissues (Armstrong et al ., 2018; Nguyen et al ., 2018; Pishas et al ., 2014), and here, we demonstrate the added capacity for cistromics. Expanding the repertoire to include the lipidome, metabolome, kinome, and secretome will provide further critical insight into tumor biology and better define the mechanism of action of pharmaceutical agents preclinically, which will lead to the identification of more clinically relevant therapeutic targets and improved translation of research findings.…”
Section: Discussionsupporting
confidence: 67%
“…An Affymetrix Human Gene 1.0 ST array containing 234 annotated snoRNAs (Affymetrix, Santa Clara, CA USA) was used to identify snoRNAs that were differentially expressed following the manufacturer’s instructions as previously described [57, 69]. “Fold change” refers to the ratio of expression in induced (H1299 treated with PonA and WE-68 treated with Nutlin) versus uninduced cells.…”
Section: Methodsmentioning
confidence: 99%